Design-for-testing for improved remanufacturability - Katherine M. M. Tant; Anthony J. Mulholland; Andrew Curtis; Winifred L. Ijomah (Journal of Remanufacturing, 2019)
By definition, a remanufactured product must perform to the same (or higher) level as the original product, and must therefore be issued a warranty of the same (or longer) duration. However, many components of remanufactured products will have been subjected to regular stresses in their first cycle of use and may exhibit unseen signs of damage at a microstructural level. This may not affect the remanufactured product's performance initially but could cause it to fail before its renewed warranty expires. To combat this, we propose that the integrity of individual components is assessed non-destructively before they are consigned to storage. However, lack of remanufacture specific tools and techniques for assessment, particularly non-destructive tools, are major hindrances to this strategy. Furthermore, ease of non-destructive testing (NDT) is not currently a consideration in the design of components; components with complex geometries may therefore be difficult to test. This preview paper presents, for the first time, a framework for including NDT suitability as a design criterion at the outset of the component's lifecycle, where the geometry and surface accessibility of the component are optimised for future assessment. Ensuring that components can be easily inspected would not only allow increased confidence in the structural integrity of remanufactured products, but it would also extend the range of products suitable for remanufacturing. This paper serves as a proof of concept, examining simple inspection scenarios in order to demonstrate how the shape of components and data acquisition geometries can adversely affect the coverage of ultrasonic NDT.
Keywords: 650; Design for remanufacture; Non-destructive testing; Ultrasonics; Optimisation; Sensors; Product design